2021
DOI: 10.1016/j.ajem.2021.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Impact of early versus late administration of bamlanivimab on readmissions in patients with high-risk COVID-19

Abstract: Background Recombinant, monoclonal antibody therapies have been utilized under emergency use authorization (EUA) for the prevention of clinical decompensation in high-risk COVID-19 positive patients for up to 10 days from symptom onset. The purpose of this study was to determine the impact of the timing of the monoclonal antibody, bamlanivimab, on clinical outcomes in high-risk COVID-19 positive patients. Methods This was an IRB-approved, retrospective evaluation of adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…Rates of infusion reaction ranged from 1.0% to 2.3%. Subsequent observational studies showed similar results, ranging from 0.8% to 13.7% depending on study definitions and population [23–25,29,32 ▪ ,72,73]. Anaphylactic reactions are rare, though have also been reported [39 ▪▪ ].…”
Section: Safetymentioning
confidence: 73%
“…Rates of infusion reaction ranged from 1.0% to 2.3%. Subsequent observational studies showed similar results, ranging from 0.8% to 13.7% depending on study definitions and population [23–25,29,32 ▪ ,72,73]. Anaphylactic reactions are rare, though have also been reported [39 ▪▪ ].…”
Section: Safetymentioning
confidence: 73%
“…As these therapeutic agents became readily available, clinicians and researchers embarked on comprehensive investigations into their impact on hospitalization rates and mortality outcomes. In spring 2021, bamlanivimab was associated with reduced rehospitalizations and, in most cases, mortality within 28 days [9,10,11,12]. Later, in the fall of 2021, sotrovimab use also seemed to decrease odds of hospitalization and mortality [13,14].…”
Section: Introductionmentioning
confidence: 99%